MICROECOLOGICAL AND FUNCTIONAL ABNORMALITIES OF INTESTINES IN CHILDREN WITH CHRONIC CONSTIPATION. METHODS OF CORRECTION - E.V. Komarova (Педиатрическая фармакология, 2010)
The work contains the follow-up results obtained by the author himself. 51 children with chronic constipation were studied. A complex assessment of microecological and functional abnormalities of intestines in this pathology revealed a reduced level of short-chain fatty acids and anaerobic index, degree I and II dysbiosis, digestion disorder in small intestines. Changes in metabolic activity of intestinal microflora were in line with the functional state of GIT. One of therapy methods for chronic constipation is restoration of normal microflora of large intestines. Absorbents need to be used to influence the pathogenic microflora. Kew words: chronic constipation, treatment, enterosorbents, dioctahedral smectite, children. (Pediatric Pharmacology. – 2010; 7(6):74-76)